Evaluation of resistance to fluoroquinolones and determination of mutations in gyrA and parC genes in Escherichia coli isolated from raw milk of dairy cows with coliform mastitis in Khorasan Razavi province, Iran - Mahdie Mahdavi; Behrooz Fathi; abdollah Jamshidi; Babak Khoramian (The Iranian Journal of Veterinary Science and Technology, 2022)
The present study was performed to assess the resistance profile to fluoroquinolone and to determine mutations in gyrA and parC genes of Escherichia coli in bovine coliform mastitis. Fluoroquinolones (norfloxacin (NOR), ciprofloxacin (CIP), enrofloxacin (NFX), levofloxacin (LEV), and ofloxacin (OFL) were tested against E. coli isolates, isolated from bovine mastitis (100 milk samples) by disk diffusion method. To determine the extent of gyrA and parC mutations associated with fluoroquinolone resistance in E. coli, two isolates with the highest resistance to each fluoroquinolone were submitted for the amplification and sequencing of the quinolone resistance-determining regions (QRDRs) of gyrA and parC genes. The disk diffusion method indicated that E. coli isolates had the highest intermediate resistance to OFL (16.7%), followed by NFX and NOR (15%), while they had low resistance to CIP and LEV (3.33%). A few silent mutations in gyrA (in codons 91, 100, 111, 131, 132) and in parC (in codons 91, 157, 159) were detected in QRDRs, and mutations in nucleotides 65, 80, and 83 in gyrA, and 195, 209, 212 in parC were detected in the other isolate. These results showed an intermediate rate of resistance to fluoroquinolones in E. coli isolates from raw milk of cows with coliform mastitis